Ecophysiological performance of a threatened shrub under restored and natural conditions in a harsh tropical mountaintop environment - Castro, Silvana A. B.; Sá, Camila E. M.; Mourão, Fabiana A.; Duarte, Heitor M.; Fernandes, G. Wilson; Lemos-Filho, José P. (Acta Botânica Brasílica, 2016)
Ecophysiological responses of plants are useful for monitoring the success of ecological restoration projects that target species conservation. In this study we evaluated the ecophysiological traits of individuals of Chamaecrista semaphora from a natural population and from a site under restoration. Water potential and chlorophyll a fluorescence parameters were measured both in adult and young plants of the two populations. No difference in water potential was found between sites, but individuals in the restored site had higher water potential at predawn. Adults in the natural site presented lower daily values of potential quantum yield, indicating the occurrence of photoinhibition. Individuals in the restored site also presented higher maximum relative electron transport rate (ETRMAX). No difference was found in leaf carbon isotope discrimination values (σ13C) between plants growing in restored and natural sites, suggesting similar water use efficiency. These results indicate that C. semaphora individuals in the restored site had similar or better photosynthetic and water economy performances than individuals at the natural site. Methodologies traditionally employed to assess stress response of plants, such as chlorophyll a fluorescence and procedures used to evaluate the efficiency of water use, allowed us to verify the success of restoration procedures using an endangered species.